Women Convicted of Intimate Partner Homicide in Oromiya Regional State of Ethiopia: Profile and Associated Factors. (May 2021) - Desta, Meseret K.; Venema, Rachel M.
This study explored the factors associated with the engagement of women in intimate partner homicide (IPH) through 10 in-depth interviews with women incarcerated in three correction facilities in Oromiya Regional State of Ethiopia. In addition, key informant interviews and six focus groups involving traditional leaders, Kebele administrators, and community members help triangulate the findings. The study revealed insight into women's social, psychological, and economic status prior to their crime. Low levels of education and economic opportunity, forced marriage, marital dispute due to polygamy, spousal violence, and low levels of community support were associated with IPH. Implications for research, policy, and practice are discussed.